UPAYA PENINGKATAN MINAT BACA SISWA MELALUI MEDIA CERITA BERGAMBAR PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS IV SDN 01 CIMAHI - Elyanda Ceisa Saputri; Ambergis, Natasya; Shafila Adhalina Insan; Eugenia Gratcia Sabu Hekin; Teofilus Ardian Hopeman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Objective of this study was to increase students' interest in reading in class IVat SDN 01 Cimahi in Indonesian language subject by utilizing picture story media. The problem that became the focus was the lack of students' interest in reading. which has an impact on the low achievement of less than optimal learning outcomes. The type of method used in this research is Classroom Action Research (PTK) with a combination approach of qualitative and qualitative data. (PTK) with a combination approach of qualitative and quantitative data, which was conducted in two cycle stages in the even semester of the 2024/2025 school year. Subjects The research subjects consisted of 33 fourth grade students at SD Negeri Cimahi. Each cycle consists of four stages: planning, implementation, observation, and reflection. The instruments used included student activity observation sheets, tests, interviews, and documentation. From the results of the research, there was a noticeable in students' interest in reading. In the pre-cycle, the average interest in reading interest was only 39,39% (less interest category), then increased to reach 54,55% in cycle I (moderate interest), and reached 81,82% in cycle II (interest category). From the research results from the results of this study, it can be concluded that picture stories are effective for foster students' interest in reading.